Perioperative Identification and ligation of MAPCAs under TEE guidance: Case series of seven patients - Datt, Vishnu; Wadhwa, Rachna; Keshav, Suman; Malik, Shardha; Aggarwal, Saket; Naqvi, Ehtesham; Geelani, MA (Cardiology and Cardiovascular Medicine, 2026)
Background: Major aortopulmonary collateral arteries (MAPCAs) are systemic-to-pulmonary arteries of variable origin or size that carry blood to the lungs in complex congenital cyanotic heart defects (CCHD). Most notably CCHD involved in the MAPCAs genesis are Tetralogy of Fallot (TOF), transposition of great arteries (TGA), tricuspid atresia (TA), VSD, Pulmonary Atresia (PA) with Ventricular Septal Defect (VSD). MAPCAs are rare, and present in 4–10 per 10,000 live births and 2–3% of all CHDs. They are commonly associated with PA with VSD (50–70%), and 5–10% in patients of TOF, and most MAPCAs arise from the descending thoracic aorta (DTA). MAPCAs are essential for survival in most extremes of the lesions. These can be utilized for unifocalization (connecting to the native pulmonary system) during surgery. MAPCAs might serve as the primary sole source of blood supply to the lungs when the native pulmonary arteries are severely hypoplastic or absent. However, it needs to be ligated before or after CPB to prevent pulmonary over-perfusion, vessel narrowing, or lung damage, and low systemic perfusion pressure and tracheal bleeding during cardiac surgery. Management of MAPCAs is complex, often requires surgical ligation or embolization in Cath lab. Cardiac catheterization is a gold standard for diagnosis of the MAPCAs and their detailed anatomy, although CT angiography (CTA) is frequently used to visualize the anatomy before surgery. However, many a times either these facilities are unavailable or children are unsuitable due to poor hemodynamic in uncompensated heart failure or profound cyanosis requiring urgent surgery. It may be feasible to detect the MAPCAs on preoperative transthoracic echocardiography (TTE), although imaging them could be difficult at times due to their unpredictable site of origin and course in the mediastinum. In this study, we describe seven cases of MAPCAs diagnosis and ligation under the transesophageal echocardiography (TEE)-guidance in patients undergoing various cardiac surgical procedures (Table 1). Material and Method: 2-D, TEE view of descending Thoracic aorta (DTA) facilitates the MAPCA diagnosis and ligation. Descending aortic short and long axis view (Desc Ao LAX) were obtained at a navigation sector angle of 0, and 90- 100 degrees respectively after rotating the probe leftward from the mid-esophageal (ME) 5-chamber view, to pass all the cardiac structures and using the transducer depth to 4–6 cm to optimize the view. The color Doppler and PWD are used to confirm the MAPCAs as long tortuous vessels with flow towards and away from the probe as red and blue respectively depending upon the direction of the blood flow on color Doppler and pulse wave Doppler. Patient selection: A prospective observational study on potential cyanotic patients of more than 5 Kg, with cyanotic congenital heart defects diagnosed at GIPMER, Tertiary care institute and posted for repair of the defects were included. The included patients with TOF, PA-VSD-MAPCAs who were treated and followed up between 01/09/2022 and 31/08/2023 were used to identify patients eligible for inclusion. No exclusion criteria for patients were applied. This case series did not require approval by the Research Ethics Committee as perioperative TEE has been used routinely in cardiac OT for perioperative cardiac monitoring. An informed consent was obtained from the parents of the patients. Patient characteristics: A total of 7 patients has been included as described in table 1. Tricuspid atresia with SA VSD, OP ASD for BD Glenn (1), TA with OS ASD with hypo plastic RV for BD Glenn(1),Infundibular PS with small VSD for VSD closure for RVOT augmentation and muscle bundle excision(1), TOF underwent BD Glenn (3) and total correction including direct VSD closure, RVOT muscle bundle excision and pericardial patch RVOT augmentation (1). Results: The overall MAPCAs diagnosed and ligated in seven patients with congenital cardiac lesions who underwent various cardiac surgical procedures. The 7 patients in whom MAPCAs were diagnosed in OT by TEE belonged to age group of 1.3 yr to 20 yrs. The cardiac lesions included TOF (4). Tricuspid atresia with subaortic VSD and ostium primum ASD (1), TA with Ostium secundum ASD (1), ventricular septum defect with pulmonary stenosis PS (1). The MAPCAs were diagnosed in OR by preoperative TEE after induction of anesthesia and ligated successfully under the TEE guidance. The common sites of MAPCAs in TOF were posterior and anterior wall of DTA, in TA with VSD the site was anterior and medial wall of DTA (Video 1), and in one case they were also arising from the left subclavian artery in addition to DTA, in VSD with PS the origin was from posterior wall (Video 2). All the diagnosed MAPCAs were ligated before Glenn or total correction in 5 patients using same mid-sternotomy in 3 patients, and left thoracotomy in 2 patients. In 2 cases of TA with VSD MAPCAs were ligated after cardiac repair using left thoracotomy (Video 3). The ligation was confirmed by TEE on color Doppler examination and absence of flow velocity on pulse wave doppler. MAPCAs were ligated perioperatively and deleterious effects of their overflow were avoided like endotracheal bleed, desaturation and mortality. Video 2: DTA SAX view of TEE showing 2-3 big MAPCAS originating from the posterior wall of the DTA. Color flow Doppler reveals distal proximal end of the aorta indicating the flow toward and away from the transducer DTA-SAX- descending thoracic aorta - short axis, MAPCAs- major aorta-pulmonary collateral arteries. Conclusions: Patients with various cyanotic congenital anomalies spontaneously develop MAPCAs to provide additional blood flow to the lungs to maintain arterial oxygenation. However, these can have several deleterious effects during and after CPB like low perfusion pressure, refractory endotracheal bleeding and even death. Many a times these are missing during the cardiac catheterization, or some patients are unsuitable for the cardiac catheterization study. The MAPCAs can be effectively diagnosed in OR by the TEE, and TEE not only diagnose the MAPCAs but also guides and confirms the complete surgical ligation before or after the CPB.